Elucidation and partial NMR assignment of monosulfated maitotoxins from the Caribbean. (June 2019) - Mazzola, Eugene P.; Deeds, Jonathan R.; Stutts, Whitney L.; Ridge, Clark D.; Dickey, Robert W.; White, Kevin D.; Williamson, R. Thomas; Martin, Gary E.
Abstract: Compounds similar to maitotoxin (MTX) have been isolated from several laboratory strains of the dinoflagellate Gambierdiscus spp. from the Caribbean. Mass spectral results suggest that these compounds differ from MTX by the loss of one sulfate group and, in some cases, the loss of one methyl group with the addition of one degree of unsaturation. NMR experiments, using approximately 50 nmol of one of these compounds, have demonstrated that the 9-sulfo group of MTX is still present, suggesting that these compounds are 40-desulfo congeners of MTX. Graphical abstract: Image 1 Highlights: High-resolution LC-MS indicate the presence of maitotoxin congeners from a Caribbean Gambierdiscus spp. Retention times and MS analysis indicate they differ from maitotoxin by the loss of one sulfate group. NMR analysis indicates that the sulfate at carbon-9 is still present indicating that there is no sulfate at carbon-40. Simulation of the chemical shifts support the experimentally determined results.